Research on Psychological Wellbeing of Adolescent School Children: Perspective on Ethical Considerations - Angeline Grace G; Sujitha P (National Journal of Community Medicine, 2023)
Adolescence is a distinctive and determinative stage in human life. Adolescent period serves as a transition between childhood and adulthood during which they acquire social, cognitive and emotional skills that determine their future. During these years, adolescent children undergo lot of physical and emotional changes. The quality of the environment where adolescents grow up shapes their physical and psychological well-being. Negative impact on mental health can happen due to encounters in homes, schools or social media which increases the risk of developing mental illness. This could be because of bullying, poverty, violence and mentally ill parents or siblings. In such cases, adolescents struggle to handle their psychological health and unless they get adequate care and support from parents, teachers and peer group, their psychological wellbeing gets affected. It is estimated that 1 in 7 adolescents worldwide experience mental health conditions. However, majority of these psychological issues go unnoticed and untreated. This article highlights various ethical issues in the Researchers’ Perspective when a study was planned to assess the psychological wellbeing of adolescent school children in an urban part of Tamil Nādu, India. Knowing the ethical concerns in conducting the research on psychological wellness of adolescents will help in planning more research studies for a better understanding of the epidemiology of mental illnesses among them.